2023
DOI: 10.3390/children10020275
|View full text |Cite
|
Sign up to set email alerts
|

Levels and Determinants of Antenatal Breastfeeding Attitudes among Pregnant Women: A Cross-Sectional Study

Abstract: Breastfeeding attitudes are strong predictors of breastfeeding behavior. Gaining a deeper understanding on the levels and determinants of antenatal breastfeeding attitudes is crucial. This cross-sectional study involved 124 pregnant women at a tertiary hospital in Hunan, China. A self-administered questionnaire, the Iowa Infant Feeding Attitude Scale, the Edinburgh Postnatal Depression Scale, the Pregnancy Stress Rating Scale, the Childbirth Attitude Questionnaire, the Perceived Social Support Scale, and the B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 49 publications
1
1
0
Order By: Relevance
“…In one study, similar to our finding, the mothers' scale mean score was high and showed that their attitudes were positive (13). But in another research it was found that about one in five women had positive attitudes toward breastfeeding, while the majority had neutral attitudes (14).…”
Section: Discussionsupporting
confidence: 85%
“…In one study, similar to our finding, the mothers' scale mean score was high and showed that their attitudes were positive (13). But in another research it was found that about one in five women had positive attitudes toward breastfeeding, while the majority had neutral attitudes (14).…”
Section: Discussionsupporting
confidence: 85%
“…The results of the statistical test obtained a value of p=0.000. Based on the results data in Table 6, the success of EBI is influenced by several factors, one of which is the role of family support plays a significant role in the delivery process, culture and family support, especially the husband, to provide a boost of mental strength to pregnant women and their awareness to carry out EBI [37]- [39].…”
Section: Influence Of Family Supportmentioning
confidence: 99%